Reality Group Counseling with Confrontation and Being-Positive Techniques to Reduce Students’ Toxic Online Disinhibition - Burhanudin, Burhanudin; Sutoyo, Anwar; Japar, Muhammad (Universitas Negeri Semarang, 2022)
Most of toxic online disinhibition perpretrators see their behavior as a means of fulfilling basic needs related to fun and freedom. However, it is a negative thing since it contradicts the principles of right, responsibility, and reality. Regarding these issues, the present study strived for examining the effectiveness of reality group counseling with confrontation and being-positive techniques to reduce toxic online disinhibition behavior. It involved 18 students chosen using a purposive sampling technique and grouped into three randomly in which each consisted of six students. Their data were collected using a toxic online disinhibition scale. Based on the results of mixed ANOVA statistical test, there laid the effect of time towards the reduction of toxic online disinhibition, namely (F (1.10, 16.558) = 317.66, p<0.01). The group effect on the reduction of online toxic disinhibition was also significant (F(2, 15) = 3.96, p<0.05). In terms of time interaction, the effect result was (F (2.21, 16.558) = 21.48, p<0.01). Thus, the findings of this study have confirmed that the group with the mixed techniques gained the highest effectiveness among the other groups. Finally, the study also serves interesting implications and suggestions to consider in the practice of reality group counseling.